Impacts of the STING‐IFNAR1‐STAT1‐IRF1 pathway on the cellular immune reaction induced by fractionated irradiation. Issue 4 (20th February 2022) - Du, Junyan; Kageyama, Shun‐Ichiro; Yamashita, Riu; Hirata, Hidenari; Hakozaki, Yumi; Okumura, Masayuki; Motegi, Atsushi; Hojo, Hidehiro; Nakamura, Masaki; Hirano, Yasuhiro; Sunakawa, Hironori; Minamide, Tatsunori; et al.
Abstract: Radiotherapy (RT) combined with immune checkpoint inhibitors has recently produced outstanding results and is expected to be adaptable for various cancers. However, the precise molecular mechanism by which immune reactions are induced by fractionated RT is still controversial. We aimed to investigate the mechanism of the immune response regarding multifractionated, long‐term radiation, which is most often combined with immunotherapy. Two human esophageal cancer cell lines, KYSE‐450 and OE‐21, were irradiated by fractionated irradiation (FIR) daily at a dose of 3 Gy in 5 d/wk for 2 weeks. Western blot analysis and RNA sequencing identified type I interferon (IFN) and the stimulator of IFN genes (STING) pathway as candidates that regulate immune response by FIR. We inhibited STING, IFNAR1, STAT1, and IFN regulatory factor 1 (IRF1) and investigated the effects on the immune response in cancer cells and the invasion of surrounding immune cells. We herein revealed type I IFN‐dependent immune reactions and the positive feedback of STING, IRF1, and phosphorylated STAT1 induced by FIR. Knocking out STING, IFNAR1, STAT1, and IRF1 resulted in a poorer immunological response than that in WT cells. The STING‐KO KYSE‐450 cell line showed significantly less invasion of PBMCs than the WT cell line under FIR. In the analysis of STING‐KO cells and migrated PBMCs, we confirmed the occurrence of STING‐dependent immune activation under FIR. In conclusion, we identified that the STING‐IFNAR1‐STAT1‐IRF1 axis regulates immune reactions in cancer cells triggered by FIR and that the STING pathway also contributes to immune cell invasion of cancer cells. Abstract : We elucidated that the fractionated irradiation‐induced immune response is regulated by the STING‐IFNAR1‐STAT1‐IRF1 pathway, which includes positive feedback, and that this mechanism acts not only on cancer cells but also on surrounding PBMCs.